The Dragon King phenomenon (super-extreme outliers) in cryptocurrency. Is Bitcoin the riskier one? - Levan Raj Selva Retnam; Saiful Izzuan Hussain; Nadiah Ruza (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study was conducted to identify the existence of the phenomenon of Dragon Kings (DKs) in five notable cryptocurrencies, namely Bitcoin, Dogecoin, Ethereum, Litecoin and Ripple. DKs are meaningful extreme outliers that occasionally fall outside the Pareto or power-law distribution. These examples have been statistically identified as extreme of extreme returns that occur more frequently than the power law distribution predicts. The study uses the Pareto distribution, usually associated with extreme data, to examine the upper and lower tails of returns. The result shows that the upper and lower tails of the returns of all the cryptocurrencies studied prove the existence of the Dragon Kings mechanism. Contrary to expectations, Bitcoin has seen the most unpreditable of extreme returns compared to other cryptocurrencies. This characteristic causes Bitcoin notably challenging to forecast. The results of this study are crucial for investors to evaluate and understand the Dragon King events, which represent returns that are exceptionally extreme even among other extreme values (super-extreme) observed in these financial assets.